Iowa Birdline update, September 10, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Iowa Birdline update for September 10, 1990. Highlights of the update include sightings of a California Gull, Red Knots, a Parasitic Jaeger, Red-necked Phalaropes, and Snowy Egrets. Also of note were the sightings of an immature Little Blue Heron, a Laughing Gull, and Barn Owls, as well as observations of numerous shorebirds and Warblers. Epson - sheet feed/flatbed